2018
DOI: 10.1139/cjfas-2016-0502
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of introduced Pacific salmon and brown trout on native brook trout: an experimental and modeling approach

Abstract: Pacific salmon (Oncoryhnchus spp.) and brown trout (Salmo trutta) are introduced species stocked in the Laurentian Great Lakes. In their native range, salmon deliver material that enhances growth, alters isotopic ratios, and increases contaminant burdens of resident fish. However, whether salmon subsidies mediate interactions between competing species is unknown. Here, we employed a mesocosm experiment and a simulation model to determine if salmon tissue consumption influences brook trout (Salvelinus fontinali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…() observed that increased egg consumption was negatively correlated to resident fish Hg concentrations in SE Alaska. Prior studies have hypothesized that consumption of carcass tissue is a primary route for energy acquisition (Schindler et al., ) and contaminant exposure to stream‐resident fish (Gerig et al., ). However, if resident fish were consuming large quantities of carcass material in our study, we should observe a concomitant increase in both PCB and Hg concentrations due to the high PCB and Hg concentrations in salmon tissue (Christensen, MacDuffee, MacDonald, Whiticar, & Ross, ; Gerig et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…() observed that increased egg consumption was negatively correlated to resident fish Hg concentrations in SE Alaska. Prior studies have hypothesized that consumption of carcass tissue is a primary route for energy acquisition (Schindler et al., ) and contaminant exposure to stream‐resident fish (Gerig et al., ). However, if resident fish were consuming large quantities of carcass material in our study, we should observe a concomitant increase in both PCB and Hg concentrations due to the high PCB and Hg concentrations in salmon tissue (Christensen, MacDuffee, MacDonald, Whiticar, & Ross, ; Gerig et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have hypothesized that consumption of carcass tissue is a primary route for energy acquisition (Schindler et al., ) and contaminant exposure to stream‐resident fish (Gerig et al., ). However, if resident fish were consuming large quantities of carcass material in our study, we should observe a concomitant increase in both PCB and Hg concentrations due to the high PCB and Hg concentrations in salmon tissue (Christensen, MacDuffee, MacDonald, Whiticar, & Ross, ; Gerig et al., ). Overall, our findings suggest that differential accumulation of contaminants between salmon tissue types coupled with a dietary choice could be a primary determinant of the magnitude of bioaccumulation of biotransported contaminants by stream‐resident fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Hg in stream-resident fish decline as Hg supplied by salmon and stream-resident fish size increases (Gerig et al, 2018). In contrast, a mesocosm experiment that measured the effect of carcass consumption on Hg bioaccumulation determined that brook and brown trout Hg increased with increased salmon consumption (Gerig et al, 2017). However, similar to field studies from the Great Lakes, Dolly Varden char (Salvelinus malma) in Alaska have lower Hg concentrations as the abundance of spawning salmon increases (Cyr et al, 2016).…”
Section: Contaminant Biotransport In the Laurentian Great Lakesmentioning
confidence: 91%
“…For example, by providing access to additional spawning habitat, increasing the connectivity of tributaries to North America's Great Lakes (hereafter Great Lakes) may result in greater reproduction for invasive species such as sea lamprey Petromyzon marinus and round goby Neogobius melanostomus, a negative effect, but also increased reproduction of highly valued introduced Pacific salmonids currently stocked into the Great Lakes, namely Chinook salmon Oncorhynchus tshawytscha, coho salmon Oncorhynchus kisutch, and adfluvial rainbow trout or steelhead Oncorhynchus mykiss. Eggs and carcasses of migratory Pacific salmonids can provide an additional food resource for resident trout populations (Ivan, Rutherford, & Johengen, 2011), though the degree to which they produce a measurable increase in growth is less certain (Gerig, Weber, Chaloner, McGill, & Lamberti, 2018). Regardless of the geographic location, understanding how resident fish populations will respond to dam removals or increased fish passage is needed to inform management decisions on dam removals and river connectivity, and for informing anglers on how fish populations might respond to river connectivity changes.…”
Section: Introductionmentioning
confidence: 99%